DEVELOPING FORMULAE TO CALCULATE MIDSPAN DEFLECTION AND FAILURE LOAD OF HORIZONTALLY CURVED STEEL I-BEAMS USING MACHINE LEARNING ALGORITHMS - Ababu, Elvis M. (My University, 2023)
Horizontally curved steel I-beams exhibit a complicated mechanical response as they experience a combination of bending, shear, and torsion, which varies based on the geometry of the beam at hand. The behaviour of these beams is therefore quite difficult to predict, as they can fail due to either flexure, shear, torsion, lateral torsional buckling, or a combination of these types of failure. Curved beams also tend to experience large deflections, which lead to nonlinear strain-displacement and curvature relations. This therefore necessitates the usage of complicated nonlinear analyses in order to accurately model their behaviour. Currently, little guidance is provided by international design standards on the serviceability limit states considerations of horizontally curved steel I-beams. The American Institute of Steel Construction (AISC) provides the most thorough design guidelines on horizontally curved steel I-beams. AISC recommends the usage of finite element modelling to determine the midspan deflection, however, no guidance is provided on the type of analysis required nor the specific finite elements that have to be used to achieve realistic and reliable results. Regarding analytical formulae, most literature makes use of Castigliano’s second theorem. The shortcoming of this method is that it is quite numerically intensive, requiring difficult integrations. There is also a lack of standard analytical formulae for typical boundary and loading conditions. Literature also outlines that Castigliano’s second theorem tends to lead to overly conservative deflection estimates. It is therefore clear that there is a need to develop an updated, simple, and accurate formula in order to estimate both the capacity and deflection of horizontally curved steel I-beams.
Keywords: Horizontally Curved Steel I-Beams; Deflection Prediction; Machine Learning; Experimental Testing; Ultimate Capacity of Beams; Design Equations